Sensor network based irrigation system for real time irrigation scheduling in vegetable crops under different methods of irrigation - KUMAR, JITENDRA; PATEL, NEELAM; RAJPUT, T B S; KUMAR, MUKESH (The Indian Journal of Agricultural Sciences, 2016)
Soil moisture sensor based irrigation scheduling is relatively a new concept in India. A soil moisture sensor based wireless irrigation system was designed, developed and tested during the years 2013-15 in vegetable crops, i. e. okra, tomato, brinjal, broccoli, potato, and knol-khol on the research farm of the Precision Farming Development Centre, Water Technology Centre, Indian Agricultural Research Institute, New Delhi, India. A network of sensors was integrated with a wireless system having modified tensiometer, level sensor, controller, GSM receiver, transmitter, solenoid valve, water meter, and pump for automated irrigation scheduling. The sensor network, global system for mobile communication (GSM) and short message service (SMS) carried the data from the sensors to the user through a mobile set. This system allows the user to effectively monitor and control water application in the field via sensors and/or through a mobile phone set by sending a command in the form of message and obtaining the moisture status in the field.